Antimicrobial activity of Lactobacillus spp. metabolites on growth of two clinical isolates in vitro - Eiman A. Saeed (Al-Qadisiyah Journal of Pure Science, 2017)
Antimicrobial activity of secondary metabolites that produced by Lactobacillus spp. has been investigated against two clinical isolates of Escherichia coli and Pseudomonas aeruginosa.Acidity effect of anaerobic fermentation of lactose in raw milk to lactic acid by Lactobacillus spp. was studied. The accumulation of acid in the medium lead to lowering pH of the yoghurt that prevent growth of E. coli and P. aeruginosa. The ability of two isolates was experimented for survival in acidic, alkaline, and neutral pH, the results showed that E. coli and P. aeruginosa have no growth in acidic pH while they have heavy growth in neutral and alkaline pH.This study confirmed the presence of synergistic effect between the secondary metabolites of lactobacilli and the acidity in yoghurt, which lead to inhibitory effect on the growth of two clinical isolates.Key ward: Lactobacillus, probiotics, secondary metabolites, therapeutic effect